Role of Socio-economic Indicators in Development and Education (Journal of Education and Development, 2022)
Combinations of broad-defined indicators of wellbeing, social harmony, education, etc., have been used to provide comparative assessments of socio-economic conditions in various nations and stimulate policy changes. In this short review we compare conceptual frameworks and actual models based on subjective (social) and objective (analytical) socio-economic indicators. An interplay of subjective and objective indicators is also the basis of an approach for interdisciplinary education of young generations, particularly in nations characterized by ethnic conflicts and/or poor wealth distribution. The interaction between social and economic indicators suggests the need of a more integrated socio-economic outlook.